1998
DOI: 10.1093/emboj/17.24.7454
|View full text |Cite
|
Sign up to set email alerts
|

Control of cleavage site selection during mRNA 3' end formation by a yeast hnRNP

Abstract: Endonucleolytic cleavage of pre-mRNAs is the first step during eukaryotic mRNA 3Ј end formation. It has been proposed that cleavage factors CF IA, CF IB and CF II are required for pre-mRNA 3Ј end cleavage in yeast. CF IB is composed of a single polypeptide, Nab4p/Hrp1p, which is related to the A/B group of metazoan heterogeneous nuclear ribonucleoproteins (hnRNPs) that function as antagonistic regulators of 5Ј splice site selection. Here, we provide evidence that Nab4p/Hrp1p is not required for pre-mRNA 3Ј end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
2
1

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(121 citation statements)
references
References 70 publications
8
110
2
1
Order By: Relevance
“…In contrast to the results of Minvielle-Sebastia et al (19), but in agreement with Kessler et al (18), we find that CF IB is absolutely required not only for proper selection of the cleavage site, but also for reconstitution of even minimal cleavage activity upon the GAL7 3Ј untranslated region. We confirmed that CF IB was required for reconstitution of polyadenylation activity upon this substrate, in agreement with published reports (18,19).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In contrast to the results of Minvielle-Sebastia et al (19), but in agreement with Kessler et al (18), we find that CF IB is absolutely required not only for proper selection of the cleavage site, but also for reconstitution of even minimal cleavage activity upon the GAL7 3Ј untranslated region. We confirmed that CF IB was required for reconstitution of polyadenylation activity upon this substrate, in agreement with published reports (18,19).…”
Section: Discussionsupporting
confidence: 91%
“…3, lane 20). Although Minvielle-Sebastia et al (19) observed cleavage in the absence of Hrp1 within 3 min of starting the reaction, we observed no cleavage without Hrp1, even if the reaction was carried out to 60 min (data not shown).…”
Section: Analysis Of the Subunit Interactions Necessary For Complex Acontrasting
confidence: 68%
See 1 more Smart Citation
“…More recently, however, it has been demonstrated that Hrp1p/Nab4p is not required for cleavage per se, but for the selection of the correct cleavage site: in the absence of the protein, several cleavage sites upstream of the correct one were used [114]. Although an e¡ect on polyadenylation was found in reconstitution experiments in vitro, no polyadenylation defect was seen in vivo [114]. Genetic experiments showed direct interactions of Hrp1/Nab4 with subunits of CF IA.…”
Section: Cleavage and Polyadenylation Factorsmentioning
confidence: 99%
“…UV cross-linking of puri¢ed recombinant Hrp1p to RNA was dependent on the presence of the e¤ciency element (see Section 3.1). Hrp1p was thus suggested to be responsible for recognizing this sequence [113] (but see [114]). …”
Section: Reaction Mechanismmentioning
confidence: 99%